Enteric Nervous System Impairment in Gastroschisis - Auber, Frederic; Danzer, Enrico; Noché-Monnery, Marie-Emmanuelle; Sarnacki, Sabine; Trugnan, Germain; Boudjemaa, Sabah; Audry, Georges (European Journal of Pediatric Surgery, 2013)
Introduction After surgical repair of gastroschisis, most neonates exhibit severe intestinal dysmotility. We hypothesized that impaired development of the enteric nervous system or interstitial cells of Cajal (ICC) network contributes to impaired intestinal motility in gastroschisis. We evaluated this hypothesis in a rat model of gastroschisis.Material and Methods Gastroschisis was created surgically in rat fetuses on gestational day 18, under general anesthesia, and small bowel was harvested on day 22. Intestinal weight-to-length (IW/L) ratio, and small-bowel wall thickness were assessed. Specimens were processed for hematoxylin-eosin staining or immunohistochemistry with specific markers for neuronal cells (Hoxb5), glial cells (GFAP, S100), and ICCs (c-kit). Myenteric plexus maturation was assessed morphologically and compared with sham and control fetuses. Stage of development of the myenteric plexus was graded from 1 (mature) to 3 (very immature) comparatively with specimens from E16 to E22 control fetuses.Results Compared with sham-operated or control fetuses, gastroschisis was associated with increases in mean intestinal weight/intestinal length (IW/L) ratio, and mean thicknesses of the total, muscular, and submucosal layers of the small-bowel wall. The myenteric plexus were present in the small bowel from fetuses with gastroschisis, however all exhibited abnormal myenteric plexus maturation. Thus, of the gastroschisis fetuses, 55% had an aspect similar to the immature myenteric plexus of E19-E20 fetuses and 45% to the very immature mesenteric plexus observed in E16-E18 fetuses. When compared with sham and control groups, ICCs were less abundant in eviscerated small bowel in the gastroschisis group and often exhibited weak c-kit staining or an abnormally round shape without branches. Hoxb5, a marker for enteric neuroblasts and neuronal precursors, was expressed similarly in myenteric plexuses in all groups. S100 or GFAP staining showed the presence of glial cells within the myenteric plexuses in all groups. The S100 expression level was similar in all groups. In contrast, the GFAP expression level was higher in the gastroschisis group than in the sham and control groups.Conclusion Our results suggest that delayed maturation of the enteric nervous system combined with impaired ICC network development may largely explain the intestinal dysmotility seen in neonates with gastroschisis.
Keywords: gastroschisis; enteric nervous system; interstitial cells of Cajal; experimental models